Physiological effects of breaking up prolonged sitting time: a review - Ying GAO; Qing-yang LI; Jian WANG (Editorial Office of Chinese Journal of Public Health, 2022)
Sedentary behavior has detrimental effects on human health. Studies have found that breaking up prolonged sitting time by short bouts of exercise can bring health benefits to glucose and lipid metabolism, cardiovascular system, and cognitive function through increasing insulin sensitivity, maintaining peripheral and central blood flow, and secreting special neurotransmitters. Different frequencies, intensities and types of interruptions have been compared in terms of the physiological effects on different people. It shows that frequency is not a significant factor for people with normal glucose tolerance, while different influence occurs when prolonged sitting is interrupted by a 30-minute single bout or multiple bouts activities. Light intensity activity is sufficient to gain benefits for the elderly and type 2 diabetes patients, while its effect on younger and healthier people remains unclear. Besides walking and running, other types of activities, such as simple resistance activity and stair climbing are also favorable. Comparing the physiological effects of different interrupting methods with the theoretical basis can provide guidance for different groups of people, which is of great significance for improving the health of the sedentary population.